Narrative therapy : the social construction of preferred realities - Freedman, Jill, M.S.W.; Combs, Gene. (1996)
This book describes the clinical application of the growing body of ideas and practices that has come to be known as narrative therapy. The primary focus is on the ways of working that have arisen among therapists who, inspired by the pioneering efforts of Michael White and David Epston, have organized their thinking around two metaphors: narrative and social construction. The authors are as concerned with attitude as with technique. Believing that a solid grounding in the worldview from which narrative practices spring is essential, they begin with an overview of the historical, philosophical, and ideological aspects of the narrative/social constructionist perspective. This involves also telling the story of their own development as particular therapists in a particular part of the world during a particular historical period
The heart of the book is devoted to specific clinical practices: locating problems in their sociocultural context, opening space for alternative stories, developing stories, questioning, reflecting, thickening plots, and spreading the news. Each practice is described, located in relation to the ideas and attitudes that support it, and illustrated with clinical examples. In addition to conversations with people illustrating particular practices, three transcripts are included to show the subtle use of questions to develop alternative, preferred realities. Drawing upon the thinking of White and Epston, Karl Tomm, and others, the final chapter looks at the ethics of relationship that guide narrative therapists in the use of specific practices
1. Shifting paradigms : from systems to stories -- 2. The narrative metaphor and social constructionism : a postmodern worldview -- 3. Opening space for new stories -- 4. Story development -- 5. Questions -- 6. Questions in action : three transcripts -- 7. Reflecting -- 8. The plot thickens -- 9. Spreading the news -- 10. Relationships and ethics
Includes bibliographical references (pages 289-298) and index
Keywords: Narrative therapy; Metaphor -- Therapeutic use; Constructivism (Psychology); Postmodernism -- Psychological aspects; Psychotherapy -- Methods; Communication; Metaphor